Extreme wave height analysis using Weibull and Rayleigh distribution in some coastal areas affected by tsunami disasters and earthquakes in September 2018 at Central Sulawesi. Issue 1 (January 2021) - Mudin, Y; Labania, H M D; Rahman, Abd; Sabhan,
Abstract: One of the most important measures is the availability of data and information through research related to the analysis of extreme wave heights at each location to be built. This study aims to provide methods and information in determining extreme wave heights that have been required to be known when designing coastal structures and public infrastructure on the coast. In this study, the extreme wave height was calculated based on a wave model simulation with an incident wave scenario that has an extreme wave height at each research location. The results showed that the distribution of extreme wave height in the waters of Palu Bay, the coast of Banawa District, was closer to the Rayleigh distribution, while the waters of Sirenja District, Donggala Regency were more in accordance with the Weybull distribution. This difference is caused by the attenuation factor of wave height due to differences in coastal morphology. The attenuation value of wave height at Banawa beach reaches 53 - 78%, while in Sirenja District it is only 35 - 46% compared to the extreme wave height in the deep sea.